Quantum Mechanical Study Using the DFT Method of the Structure, Stability and Vibrationalmosion of the Ketones of Cyclopropane - Salman, Samir Addy (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this study a DFT calculation on cyclopropanone, cyclopropandione and cyclopropantrione molecules was performed using the basis function 6-31G ** / MP2 and exchange correlation potential B3-LYP. The results showed that the ground state of all molecules geometry belong to the point group ð¶2ð‘£where a vibronic coupling between the vibrational motion with the electronic ground state in the molecule C3O3 this leads to a reduction in symmetry of the molecule fromð·3â„Žto ð¶2ð‘£, the driving force of this process is accessing to the electronic configuration complies with HÃ¼ckel aromatic systems with two electrons. Also in this, study the normal modes of vibration, frequencies, intensities and symmetry species. Finally the strain angular energy of molecules was calculated in a manner of isodesmic reaction